Buoyancy Influence on Fully Developed Laminar Mixed Convection between Vertical Parallel Plates - Ganjikunta Aruna (Research Updates in Mathematics and Computer Science Vol. 8, 2024)
The novelty of this research work is to study the buoyancy effects on fully developed mixed convection which is a laminar flow between two vertical plates with a transverse magnetic field in the presence of up and downwards flow is studied. With the technological demand for heat transfer enhancement, most markedly related to compact heat exchanges, solar energy collection, as in the conventional flat plate collector and cooling of electronic equipment analysis, the parallel-plate channel geometry gained further attention from thermal engineering researchers. The buoyancy effects on fully developed laminar mixed convection in vertical channels are considered. The flow governing equations are solved by using the finite difference method. The velocity, the temperature and the Pressure profiles are presented graphically for different values of governing parameters like buoyancy parameter Gr/Re, The wall temperature difference ratio rT, and Prandtl number Pr and their behaviour is discussed. The results of this study highlight how crucial it is to take thermal boundary conditions and buoyancy effects into account when forecasting and comprehending fluid flow and heat transfer processes in vertical channels. By advancing our understanding of fluid dynamics and thermal sciences, these findings allow for more precise modeling and design of linked engineering systems.